Diagnostic block and radiofrequency ablation of the acromial branches of the lateral pectoral and suprascapular nerves for shoulder pain: a 3D cadaveric study. Issue 4 (11th February 2021) - Tran, John; Peng, Philip; Agur, Anne; Mittal, Nimish
Abstract : Background and objectives: Acromial branches of the lateral pectoral and suprascapular nerves have been proposed as targets for diagnostic block and radiofrequency ablation to treat superior shoulder pain; however, the nerve capture rates of these procedures have not been investigated. The objectives of this study were to use dissection and 3D modeling technology to determine the course of these acromial branches, relative to anatomical landmarks, and to evaluate nerve capture rates using ultrasound-guided dye injection and lesion simulation. Methods: Ultrasound-guided dye injections, targeting the superior surface of coracoid process and floor of supraspinous fossa, were performed (n=5). Furthermore, needles targeting the superior and posterior surfaces of the coracoid process were placed under ultrasound guidance to simulate needle electrode position (n=5). Specimens were dissected, digitized, and modeled to determine capture rates of acromial branches of lateral pectoral and suprascapular nerves. Results: The course of acromial branches of lateral pectoral and suprascapular nerves were documented. Dye spread capture rates: acromial branches of lateral pectoral and suprascapular nerves were captured in all specimens. Lesion simulation capture rates: (1) when targeting superior surface of coracoid process, the entire acromial branch of lateral pectoral nerve was captured in all specimens and (2) when targeting posterior surface of coracoid process, the acromioclavicular and bursal branches of acromial branch of suprascapular nerve were captured in all specimens; coracoclavicular branch was captured in 3/5 specimens. Conclusions: This study supports the anatomical feasibility of ultrasound-guided targeting of the acromial branches of lateral pectoral and suprascapular nerves. Further clinical investigation is required.